Recurrent Thyroid Carcinoma in a Dog - Diagnosis by 18F-Fluorodeoxyglucose Positron Emission Tomography - Yu, Hogeun; Chae, Yeon; Yun, Taesik; Koo, Yoonhoi; Lee, Dohee; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Acta Scientiae Veterinariae, 2023)
Background: Thyroid tumor is a common endocrine tumor that accounts for up to 3.8% of all tumors in dogs. Most of them are malignant and usually nonfunctional in dogs. 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) is an imaging modality that detects intracellular accumulation of radioactive deoxyglucose administered in the body and is used in combination with computed tomography to provide functional information with exact anatomical localization. It is used in human medicine to detect residual or recurrent head and neck neoplasm after treatments, such as surgical resection. This report describes the first case of diagnosing recurrent thyroid carcinoma (TC) through FDG-PET in a dog. Case: A 9-year-old castrated male Maltese dog presented with a palpable mobile mass in the right ventral cervical region. Radiography and ultrasonography (US) showed a radiopaque mass adjacent to the trachea, and the right thyroid gland was enlarged on computed tomography. The surgically excised mass was encapsulated and measured to be 2.3 × 1.0 × 3.4 cm (width x length x height) in size. Histopathologically, the mass was diagnosed as differentiated follicular TC, and gross and vascular invasions were observed. To prevent recurrence, postoperative carboplatin chemotherapy was performed for 5 months. Two months after completion of chemotherapy, a nodule of approximately 7 mm in diameter was detected in the thyroidectomy bed by US. FDG-PET scanning was performed as an effective means of evaluating the malignancy, local recurrence, and metastasis of differentiated follicular TC. The nodule had the dimensions of 2.8 × 5.9 × 8.6 mm, a maximum standardized uptake value (SUV) of 8.49, and a mean SUV of 5.6. The results of FDG-PET suggested the recurrence of TC; therefore, the second chemotherapy protocol using toceranib was applied for 16 months. After initiation of the second chemotherapy, follow-up examinations were conducted approximately every 4 months. On the 134th day, although the nodule was not palpated, its size was observed to have increased to 5.0 × 3.8 × 13.6 mm on cervical US on the 232nd day, showing heterogeneous and hypoechoic parenchyma. On the 405th day, the tumor was enlarged to a size of 13.4 × 12.9 × 22 mm and identified as a lobular, amorphous shape, and its heterogeneity was increased. Moreover, two pulmonary nodules with well-defined margins were found on radiography in the left caudal lung lobe (9 × 10 mm and 12 × 12 mm [width × length]); thus, lung metastasis was suspected. On the 536th day, anorexia and lethargy occurred, and the dog was lost to follow-up. Discussion: In the present case, local recurrence of TC was suspected based on cervical US. Although US was useful as a screening tool, additional examinations were necessary for evaluating local invasiveness, malignancy, and nodal/distant metastasis. FDG-PET can detect recurrence at an early stage because it can sense increased tumor metabolism through physiologic absorption of FDG, even before the beginning of anatomic change in the lesion. Therefore, FDG-PET can assist in treatment planning and provide better prognosis. In humans, focal FDG uptake and a high maximum SUV in the thyroid gland on FDG-PET were associated with a higher risk of cancer. Because there was no evidence of neoplasia except the thyroid lesion during the FDG-PET examination, the tumor showed an increasingly malignant pattern of the thyroid gland on US during the follow-up period, and the metastatic pulmonary nodules were identified on the 650th day after the thyroidectomy. Therefore, the present case was diagnosed as recurrent TC. This report describes the use of FDG-PET for diagnosing local recurrence of TC, pointing to FDG-PET as a potential strategy to evaluate loco-regional recurrence and distant metastasis of TC. Keywords: canine, FDG-PET, follicular thyroid carcinoma, metastasis, tumor, cancer.